PENGARUH KARAKTERISTIK INDIVIDU DAN KETERPAJANAN INFORMASI KELUARGA BERENCANA OLEH PETUGAS KB TERHADAP PENGAMBILAN KEPUTUSAN MENGGUNAKAN KONTRASEPSI ISTRI DI SUMATERA SELATAN - VIYA YANTI MALA (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2020)
ABSTRACT The decision to use contraception can vary according to the level of understanding of husband and wife to the concept of family planning. Therefore it is necessary to know the factors that influence decision making in the family, because this will affect the sustainability of family planning programs in the future. In bivariate analysis (chi square test) only 3 factors have a significant effect, namely age of first marriage, area of ​​residence, and knowledge of family planning, while other factors, such as age, education, occupation, wealth quintile, number of children, taking decisions, and exposure to family planning messages by family planning staff do not have a significant effect on contraceptive use. The results of the research show that the husband's influence is still strong in making decisions related to women's reproductive health. This condition shows the strong influence of gender and culture in a family. Perception of the value of children, namely as future investments and children as current investments affect family decisions in determining the number of children desired. Keywords: Decision making, wife contraception, family planning